PENGARUH PENGALAMAN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ARTA BOGA CEMERLANG KOTA BENGKULU - Eti Arini; Hawin Yeni Roiselina (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
The purpose of this study was to determine the effect of work experience and work ability on employee performance at PT.Arta Boga Cemerlang, Bengkulu City. This study uses quantitative methods and data collection by means of observation, interviews and questionnaires. The population in this study were all employees of PT. Arta Boga Cemerlang, Bengkulu City, totaling 60 people and sampling using the saturated sampling method. Based on the results of multiple linear regression, the regression equation form Y = 4.522 + 0.370 (X1) + 0.546 (X2). This equation can be explained by the positive influence of each independent variable, namely Work Experience (X1) and Work Ability (X2) on employee performance (Y). And the coefficient of determination of R2 = 0.653 or approximately (65,3%) through hypothesis testing together (simultaneously) and individually (partial) in this study using the t test and f test, Work Experience (X1) and Work Ability ( X2) = 0.000, it means that the value of Fsig <0.05 indicates jointly and has a significant effect.Keywords: Work Experience, Work Ability, Employee Performance